PENGARUH BAHAN BAKU TERHADAP TINGKAT PRODUKSI GULA MERAH DI DESA SALUTA KECAMATAN GALELA UTARA - Posi, Sahrul; Tayana, Sri Hartaty; Manoma, Suharli (CV. Era Digital Nusantara, 2024)
The purpose of this study was to determine the effect of raw materials on the level of brown sugar production in Saluta Village, Galela Utara District. This type of research is a quantitative research with a descriptive approach. This study uses primary data by distributing questionnaires to respondents. The sample technique used in this study was a simple random sampling method (Simple Random Sampling), that is, all populations have the same opportunity to be selected as samples. The sample in this study consisted of 85 respondents. Data were analyzed using multiple linear regression analysis and data testing was performed using the Statistical Package for Social Science (SPSS) program. The results showed that raw materials had a positive and significant effect on brown sugar production. The results of the statistical analysis show that the tcount is 4.028 which is greater than the ttable 1.992 and the significant value is 0.000 which is less than 0.05.